2022
DOI: 10.3390/molecules27134231
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear Tricoordinate Copper(I) and Silver(I) Halide Complexes of a Sterically Bulky Thiourea Ligand and a Computational Insight of Their Interaction with Human Insulin

Abstract: Reaction of two equivalents of the bulky 1,3-bis(2,6-diethylphenyl)thiourea ligand (L) with MX (being M = Cu+, Ag+; and X = Cl−, Br−, I−) in acetonitrile afforded neutral complexes of the type [MXL2] [CuClL2].2CH3CN (1a); [CuBrL2].2CH3CN (1b); [CuIL2] (1c): [AgClL2] (2a); [AgBrL2] (2b) and [AgIL2] (2c). The two aromatic groups in free ligand were found to be trans with respect to the thiourea unit, which was a reason to link the ligand molecules via intermolecular hydrogen bonding. Intramolecular hydrogen bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…However, there is no change in the protein structure such as compaction as a result of the addition of atoms such as H (1.0078 Da), Na (22.9898 Da), and K (38.9637 Da), which are smaller than the copper atom. These results showed that copper metal and alkali metals interact with insulin protein in different ways in the gas phase and this difference can be monitored through conformational changes with IM-MS analysis [30][31].…”
Section: Resultsmentioning
confidence: 91%
“…However, there is no change in the protein structure such as compaction as a result of the addition of atoms such as H (1.0078 Da), Na (22.9898 Da), and K (38.9637 Da), which are smaller than the copper atom. These results showed that copper metal and alkali metals interact with insulin protein in different ways in the gas phase and this difference can be monitored through conformational changes with IM-MS analysis [30][31].…”
Section: Resultsmentioning
confidence: 91%
“…In silico and molecular docking studies have shown that divalent metal complexes being active antiviral agents and immunity enhancers can be very effective against SARS-CoV-2. [39] , [40] , [41] Considering the potential bioactivities of the thiourea derivatives [ 42 , 43 ], we have extended our findings to divalent metals (Co, Ni, Pd and Zn) using symmetrically substituted bulky ligand, N,N ′-bis(2,6-diethylphenyl)thiourea [44] . In addition to their syntheses, structural characterization and Hirshfeld analyses, we have applied molecular docking approach to evaluate the binding and interaction abilities of the reported compounds as a starting point for the in silico drug discovery.…”
Section: Introductionmentioning
confidence: 83%